Stimulation and Recording Electrodes for Neural Prostheses - Pour Aryan, Naser; Kaim, Hans; Rothermel, Albrecht (SpringerBriefs in Electrical and Computer Engineering,, 2015)
This book provides readers with basic principles of the electrochemistry of the electrodes used in modern, implantable neural prostheses. The authors discuss the boundaries and conditions in which the electrodes continue to function properly for long time spans, which are required when designing neural stimulator devices for long-term in vivo applications. Two kinds of electrode materials, titanium nitride and iridium are discussed extensively, both qualitatively and quantitatively. The influence of the counter electrode on the safety margins and electrode lifetime in a two electrode system is explained. Electrode modeling is handled in a final chapter.